2007
DOI: 10.1152/jn.00267.2007
|View full text |Cite
|
Sign up to set email alerts
|

Multidigit Control of Contact Forces During Transport of Handheld Objects

Abstract: When an object is lifted vertically, the normal force increases and decreases in tandem with tangential (load) force to safely avoid slips. For horizontal object transport, horizontal forces at the contact surfaces can be decomposed into manipulation forces (producing acceleration/deceleration) and grasping forces. Although the grasping forces must satisfy equilibrium constraints, it is not clear what determines their modulation across time, nor the extent to which they result from active muscle contraction or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 24 publications
(32 reference statements)
3
11
0
Order By: Relevance
“…By dissociating these two components, the authors reported that during the initial accelerating phase of the movement the grasping force increased slowly if at all, reaching its maximum value only midway during the movement, i.e., at peak velocity (zero acceleration). A temporal coincidence between the peak of grasping force and the peak of velocity for horizontal movements was also reported by Gao et al (2005) and by Winges et al (2007). A dissociation between manipulating and grasping components of the grip was adopted in a double-step experiment (Danion and Sarlegna 2007) to ascertain whether grasp force corrections precede or follow arm movement corrections.…”
Section: Unimanual Gripmentioning
confidence: 79%
See 2 more Smart Citations
“…By dissociating these two components, the authors reported that during the initial accelerating phase of the movement the grasping force increased slowly if at all, reaching its maximum value only midway during the movement, i.e., at peak velocity (zero acceleration). A temporal coincidence between the peak of grasping force and the peak of velocity for horizontal movements was also reported by Gao et al (2005) and by Winges et al (2007). A dissociation between manipulating and grasping components of the grip was adopted in a double-step experiment (Danion and Sarlegna 2007) to ascertain whether grasp force corrections precede or follow arm movement corrections.…”
Section: Unimanual Gripmentioning
confidence: 79%
“…More specifically, Winges et al (2007) and Slota et al (2011) questioned the notion of model-based predictions by suggesting that the modulation of grasp force can be explained more simply by taking into account the elastic forces arising from muscle co-contraction. Along similar lines we ask whether a parsimonious account of the experimental findings may be derived from the assumption that the forces generated in both point-to-point and circular movements can be described as the response of viscoelastic systems to appropriately tailored driving inputs.…”
Section: Can We Do Without Predictive Control?mentioning
confidence: 99%
See 1 more Smart Citation
“…Authors suggested that coupling between proximal and distal muscles played a role in this directional tuning. Subsequent EMG studies showed that horizontal transport was achieved by feedforward stiffness modulation (Winges et al 2007a), which was potentially mediated by coupling between proximal arm muscles and intrinsic hand muscles (Winges et al 2007b). These coordination patterns extend to more complex circular movements, where grip force reflects the additive effects of the vertical and horizontal movement components (Slota et al 2011).…”
Section: Impact Of Proximal Arm Kinematics On Spatial Coordination Ofmentioning
confidence: 99%
“…In robotics, the manipulation and internal forces are controlled independently (Kerr & Roth, 1986; Yoshikawa & Nagai, 1991). In contrast, people modulate the internal forces with the manipulation force (Smith & Soechting, 2005; Gao et al, 2005; Winges et al, 2007; Gorniak et al, 2010). For example, during vertical object manipulation the grasping pinch forces scale linearly with the effective load force, which depends on the acceleration (Johansson et al, 1992; Flanagan et al, 1993; Flanagan & Tresilian, 1994; Smith & Soechting, 2005).…”
mentioning
confidence: 99%